NEGLECT OF STRUCTURAL COMFORTS IN LIBRARIES - Aswath, Lalitha (Malaysian Journal of Library and Information Science, 1999)
Examines the planning of space for different functions in three UGC-financed university libraries, located in Karnataka State, India. Planning aspects have been analysed on the basis of recommendations made by University Grants Commission (India), and standards provided by Indian Standards Institution. The findings indicate that the planners have not given due thought to the application of ISI standards and UGC recommendations made for different types of buildings resulting in a lot of wastage of space.